Maternal concepts and expectations regarding a preterm infant - Pereira Padovani, Flávia Helena; Martins Lindares, Maria Beatriz; Duarte Pinto, Ingrid; Duarte, Geraldo; Martinez, Francisco Eulógio (The Spanish Journal of Psychology, 2008)
The objective of the present study was: (a) to identify the concerns, verbally expressed, of 50 mothers regarding their preterm infants (PT) and then compare their verbal expression with those of 25 mothers of full-term infants (FT); and (b) to correlate the mothers’ verbal expressions with maternal and infant variables. The following instruments were used to compose and characterize the sample: Structure Clinical Interview for DSM III-R Non-Patient (SCID/NP), State-Trait Anxiety Inventory (STAI), Beck Depression Inventory (BDI), and medical charts. Results showed that there was no difference between groups in term of mothers’ expectations and conceptualizations; both groups exhibited predominantly positive expectations and concepts. In comparison with FT mothers, PT mothers verbally expressed more feelings and reactions predominantly negative or conflicting in relation to infant birth. Higher levels of maternal anxiety and depression in the PT Group were correlated with more verbal expressions about negative or conflicting emotions. In addition, lower birth weight, higher neonatal risk and longer length of stay in intensive care nursery of the infants were related with more negative or conflicting concepts by the mothers.